The function of the lateral inhibitory mechanisms in the somatosensory cortex is normal in patients with chronic migraine. Issue 4 (April 2020) - Coppola, Gianluca; Cortese, Francesca; Bracaglia, Martina; Di Lorenzo, Cherubino; Serrao, Mariano; Magis, Delphine; Pierelli, Francesco
Highlights: A concurrent peripheral SSEP paradigm was used to study lateral inhibition (LI) in chronic migraine (CM) patients. At the group level, our data refute the hypothesis that LI mechanisms are atypical in CM. Despite this, we did find significant correlations between LI and clinical migraine features. Abstract: Objective: To study lateral inhibition and habituation/sensitization in the somatosensory cortex of patients with chronic migraine (CM) and to identify correlations with clinical migraine features. Methods: Sixteen patients with CM without medication overuse, and 17 healthy volunteers (HVs) received somatosensory evoked potentials (SSEPs) elicited by separate electrical stimulation of the right median (M) and ulnar (U) nerves at the wrist and by simultaneous nerve stimulation (MU). We measured the N20–P25 amplitudes and calculated the lateral inhibition (LI) percentage using the formula {100–[MU/(M + U) * 100]}. We also calculated sensitization (SSEP amplitude during block 1) and delayed habituation to M-nerve stimulation. Results: The percentage of LI did not differ between the groups (40.2% in HV, 47.4% in CM, p  = 0.276) and was negatively correlated with the monthly headache-day number ( r  = −0.532, p  = 0.034). Patients showed a generalized increase in SSEP amplitudes compared to HVs and habituated normally. Conclusions: We showed a pattern of somatosensory response in CM similar to that observed during attacks of episodic migraine. Significance: In the transition process between episodic migraine and CM, LI attempts to physiologically counteract the mounting increase in attack frequency, but this is insufficient to allow patients to exit the chronic phase.